2023
DOI: 10.5530/001954641895
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Telepharmacy Services in Community Pharmacy – Pharmacists’ Perspective in Republic of Serbia

Abstract: Aim/Background: COVID-19 pandemic has casted a new light over the capacity of telepharmacy to increase access to pharmaceutical care, providing more support to patients and allowing new opportunities for pharmacists. However, telepharmacy still hasn't been introduced as a standardised pharmaceutical service in the Republic of Serbia, therefore, the objective of this paper is to assess the potential for its local implementation by exploring the perspectives of community pharmacists. Materials and Methods: Semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Most respondents ready to use telepharmacy were young pharmacists. This was supported by the research findings from Ilkic et al, which stated that young pharmacists tended to be more ready to use telepharmacy technology [29] . Before implementing telepharmacy, training or incorporating telepharmacy practice into the education program should be considered, such as a telepharmacy applicative case study [30] .…”
Section: Readiness To Implementation Of Telepharmacymentioning
confidence: 59%
“…Most respondents ready to use telepharmacy were young pharmacists. This was supported by the research findings from Ilkic et al, which stated that young pharmacists tended to be more ready to use telepharmacy technology [29] . Before implementing telepharmacy, training or incorporating telepharmacy practice into the education program should be considered, such as a telepharmacy applicative case study [30] .…”
Section: Readiness To Implementation Of Telepharmacymentioning
confidence: 59%
“…Ng and Sze reported that community pharmacists who are younger and have fewer years of experience in the workforce are more likely to have a favorable outlook toward the adoption of telepharmacy [ 32 ]. Telepharmacy services would appeal mainly to younger pharmacists, according to Ilki et al [ 33 ]. Continuing professional education is a relevant venue to increase knowledge and promote a positive attitude towards telepharmacy, especially for older pharmacists.…”
Section: Discussionmentioning
confidence: 99%